Appreciative Inquiry Analysis Through SOAR Approach In The Lens Of Shariah In Facing Industry 4.0 On Indonesia’s Islamic Banking - Zulfikar, Zulfikar (Institut Agama Islam Negeri Madura, 2021)
The research I conducted looked at how the impact of the industrial revolution 4.0 on the Islamic banking sector. In this case, I took a SOAR analysis approach (strengths, opportunities, aspirations and results), in contrast to the SWOT analysis, SOAR analysis resembled more at the advantages and opportunities of Islamic banking in achieving progress not only the world but also the hereafter. The SOAR analysis that I did combines with Sharia principles that will realize as in digital financing products and internet banking. The Sharia Supervisory Board and DSN-MUI are among the regulators making sharia banking stronger and recognized. Virtually a usury-free bank and towards the benefit of the Ummah both in the world and in the hereafter. The different method I use is a qualitative method by viewing at and analyzing the research object to be examined.